Understanding wine chemistry - Waterhouse, Andrew Leo, 1955-; Sacks, Gavin L., 1978- (Wiley, 2016)
Wine chemistry inspires and challenges with its complexity, and while this is intriguing, it can also be a barrier to further understanding. The topic is demystified in Understanding Wine Chemistry, which explains the important chemistry of wine at the level of university education, and provides an accessible reference text for scientists and scientifically trained winemakers alike.